ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN EMESIS GRAVIDARUM MELALUI PEMBERIAN AROMATERAPI PEPPERMINT DI PUSKESMAS TANJUNG BALAI KARIMUN - Puti Lenggo Geni; Dian Juni Ekasari; Dyka Aidina (Universitas Batam, 2023)
The incidence of emesis gravidarum in 2015 according to the World Health Organization (WHO) is 12.5% ​​of all pregnancies in the world. . Cases of nausea and vomiting in pregnancy in Indonesia reach 50-90%. In primigravidas complaints of nausea and vomiting occur in 60 - 80% of pregnancies while in multigravidas it occurs in 40 - 60% of pregnancies. Peppermint is known to be a safe and effective drug for treating nausea and vomiting in pregnant women. The purpose of this study was to provide midwifery care to pregnant women comprehensively and continuously by applying peppermint aromatherapy to reduce emesis gravidarum in first trimester pregnant women. The case report in this case study used the case study method. The study was conducted at the Tanjung Balai Karimun Health Center in March 2023. The subject used in this case study was Mrs A, a pregnant woman with emesis gravidarum. The data collection methods included participatory observation, interviews, measurements, documentation. The provision of midwifery care to pregnant women with emesis gravidarum through giving peppermint aromatherapy has been carried out. After reviewing the case and evaluating the case, there is no gap between theory and practice in the field. The results of the study found that the mother wanted to use peppermint aromatherapy to reduce the nausea and vomiting she was experiencing.